2003
DOI: 10.1084/jem.20030615
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Cooperates with the B Cell Linker Protein SLP-65 as a Tumor Suppressor in Pre-B Cells

Abstract: Expression of the pre-B cell receptor (pre-BCR) leads to activation of the adaptor molecule SLP-65 and the cytoplasmic kinase Btk. Mice deficient for one of these signaling proteins have an incomplete block in B cell development at the stage of large cycling pre-BCR+CD43+ pre-B cells. Our recent findings of defective SLP-65 expression in ∼50% of childhood pre-B acute lymphoblastic leukemias and spontaneous pre-B cell lymphoma development in SLP-65−/− mice demonstrate that SLP-65 acts as a tumor suppressor. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 30 publications
10
123
1
Order By: Relevance
“…BLNK -/-Btk -/-mice were affected with this malignancy at a higher rate (6/21, or 29%) by 16 wk (Fig. 4A-D), consistent with previous studies [23,30]. A similar frequency of BLNK -/-PLCc2 -/-mice (4/13, or 31%) became visibly ill or died by 16 wk (Fig.…”
Section: Differential Roles For Btk and Plcc2 In Pre-b Cell Tumor Supsupporting
confidence: 90%
See 1 more Smart Citation
“…BLNK -/-Btk -/-mice were affected with this malignancy at a higher rate (6/21, or 29%) by 16 wk (Fig. 4A-D), consistent with previous studies [23,30]. A similar frequency of BLNK -/-PLCc2 -/-mice (4/13, or 31%) became visibly ill or died by 16 wk (Fig.…”
Section: Differential Roles For Btk and Plcc2 In Pre-b Cell Tumor Supsupporting
confidence: 90%
“…Some BLNK -/-mice develop pre-B lymphoma [21]. This occurs at a higher rate in the absence of Btk [23], indicating a BLNK-independent role for Btk as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data show that up to 15-fold overexpression of human BTK in BtkÀ/À mice actually functions as tumor suppressor gene. 53,54 This level of expression far exceeds what is reached with EFS and CD19 promoters but is lower than that with the viral SFFV promoter. With this promoter, levels of BTK expression were very high and 80% of mice developed erythromyeloid proliferations within a few weeks after transplantation.…”
Section: Discussionmentioning
confidence: 93%
“…In the absence of SLP65, B cell development is arrested at the pro-B to pre-B cell transition (Minegishi et al, 1999;Pappu et al, 1999), which parallels complete breakdown of (pre-) B cell receptor signaling in SLP65-deficient B cells (Ishiai et al, 1999;Pappu et al, 1999;Hayashi et al, 2003). While one study reported normal expression of SLP65 in childhood acute lymphoblastic leukemia (Imai et al, 2004), recent work by us and others Hayashi et al, 2003;Jumaa et al, 2003;Kersseboom et al, 2003;Klein et al, 2004) indicated a role of SLP65 as a tumor suppressor in human and murine leukemia derived from pre-B cells. Based on these findings, we investigated (i.)…”
Section: Introductionmentioning
confidence: 97%